Aid withdrawal as punishment for defaulting sovereigns? An empirical analysis - Jana Brandt; Markus Jorra (Philipps-University Marburg, Faculty of Business Administration and Economics, 2012)
This paper empirically investigates whether donor countries punish sovereign defaults by reducing foreign aid ows. Our findings reject the hypothesis formulated in the theoretical literature that a default leads to a loss of foreign aid for the defaulting country. Creditor countries directly affected by the default do not reduce their aid disbursements. Hence, foreign aid is not used as a punishment instrument. Neither can it therefore serve as an enforcement mechanism for international debt contracts. Furthermore, other donors even raise the amount of development assistance allocated to the delinquent country by about 15% on average. Overall the amount of foreign aid given to the defaulting country increases by 6.4%.
Keywords: F34; F35; C23; C24; 330; Sovereign defaults; Default costs; Foreign aid; Sanctions; Entwicklungshilfe; Internationale Wirtschaftshilfe; Staatsbankrott; Welt